Performance Evaluation Of An Agitated Thin Film Evaporator For Pineapple Juice Concentration - Emhamed, Ibrahim Greiby (2004)
Concentration is one of the important operations in food industry with applications ranging from the production of condensed milk, paste and purees from fruits. Using an agitated thin film evaporator allows for the concentration to be undertaken at low temperature and short residence time with reduced heat loss for heat sensitive material. The parameters that influence an agitated thin film evaporator process are steam temperature; product feed rate, vacuum pressure, rotor speed, physical and thermal properties of the product and the overall heat transfer coefficient. These indicate that the process is a very complex heat and mass transfer an operation that requires optimization in order to reduce the cost and maintain the product quality The overall heat transfer coefficients (U,) of pineapple juices (fresh juice of 11.3, 14.4, 19.9. and 27.3 "Brix) were determined using a laboratory scale agitated thin film evaporator (ATFE) under different rotational speeds (200, 400, and 600 rpm),liquid flow rates (25, 35, and 45 Ilh), and at constant steam and vacuum pressure. The Experiments were conducted with water and (U,) for water determined under the different parameters. S ~ meq uations to predict the Thermophysical properties of the pineapple juices at different concentrations were derived from the experimental data (density and viscosity) and others taken from the literature. The overall heat transfer coefficients (U,) were determined based on inner heat surface area. The magnitude of (U,) ranged from 390 to 2700 W / m" CTh. e performance of the evaporator was evaluated and determined .Some of the pineapple juices quality parameters before and after concentration were studied for effects of concentration by ATFE .The juice color was very little changed based on the Hunter lab values measurements, while the vitamin C contents were decreased by 10.1 %, and 23.13% for the 16.8 and 40.3 "Brix ,respectively